Sistema integrado para la gestión de indicadores de calidad para la facultad Ciencias de la Ingeniería y Aplicadas, Módulo Academia. - Guamushig Jaque, Klever Mauricio (2019)
The present technological project is directed to the development of the management system of quality indicators. In this way, the concept which is has about the topic is that allows it for evaluating the decision-making by performance within an organization. The software will allow getting systematized systems for administrators in the distribution field from Teaching Work at Engineering and Applied Sciences Department at the Technical University of Cotopaxi; it will facilitate the use of information. The objective from technological proposal is the systematization of the administrative management processes, through the computer technologies use that provide planning and activities management, evaluating teachers of the four careers of the Institution of Higher Education. For the software development has been used the SCRUM methodology, insomuch it allows to streamline the software development for the application construction. It has used tools like HTML and PHP; these are programming tools and allow getting a better user experience. BootStrap program was manipulated, which is an open code for website designs and web applications. Significantly, is a information storage means that has been considered motor use the MySQL database. The got result is the quality indicator systematization based on the Academia criterion and its two sub-criteria of Teaching Quality and Dedication. It is concluded that given the computer need of the CIYA Faculty, the implementation this developed system will allow the information processing correspondent to the academic management in a fast, reliable and safe manner reducing time in the delivery of dossiers or accounts, which require quality indicators.